Engaging with the other: student reflections on intercultural communication - Dalib, Syarizan (2019)
With the advanced technology and new information becoming much of global trend today, intercultural communication becomes more pertinent.There is a need to explore students’ interest to engage with ‘the other’ and their ways of communicating in multiple spaces they are in, particularly in the campus.Drawing from student self-reflections within focus groups, this paper highlights their experiences on engaging with the other and their views on intercultural competence.The paper ends with several implications on intercultural communication and intercultural competence among students in today’s interconnected world.